Preparation of Monolithic Cu(In0.7Ga0.3)Se-2 Nanopowders and Subsequent Fabrication of Sintered CIGS Films - Song, Bong-Geun; Jung, Jae Hee; Bae, Gwi-Nam; Park, Hyung-Ho; Park, Jong-Ku; Cho, So-Hye (AMER SCIENTIFIC PUBLISHERS, 2013)
Cu(In,Ga)Se-2 (CIGS) is a compound semiconductor and is one of the most attractive light-absorbing materials for use in thin film solar cells. Among the various approaches to prepare CIGS thin films, the powder process offers an extremely simple and materials-efficient method. Here, we report the mechano-chemical preparation of CIGS compound powders suitable for fabrication of CIGS films by a powder process. We found that the CIGS phase was formed from the elemental powders of Cu, In, and Se and liquid Ga using high energy milling process with a milling time as short as 40 min at 200 rpm due to a self-accelerating exothermic reaction. The morphology and size of the CIGS powders changed with a function of the milling speed (100-300 rpm), leading to an optimal condition of milling at 200 rpm for 120 min. We also found that it was difficult to obtain a monolithic phase of the CIGS powders without severe particle aggregation by nnechano-chemical milling alone. Therefore, in combination with the milling, subsequent heat-treatment at 300 degrees C was performed, which successfully provided monolithic CIGS nanopowders suitable for powder process. When a thin film was fabricated from the monolithic CIGS nanopowders, a highly dense film with large crystalline grains was obtained. The CIGS film preserved its chemical composition of CuIn0.7Ga0.3Se2 after sintering as evidenced by Raman spectroscopy, EDS and SAED pattern of transmission electron microscopy. The film was also found suitable for a light absorbing layer of CIGS solar cells with its band gap energy of 1.14 eV evaluated by transmittance spectroscopy.
Keywords: CU(IN,GA)SE-2 THIN-FILMS; SOLAR-CELLS; LAYERS; ROUTE; CIS